Information in geographical space as the basis of cross-disciplinary researches in culture Geography - Аlina N. Paranina; Roman V. Paranin (European Journal of Geography, 2017)
This article contains an attempt to integrate the ideas of structural processes within the boundaries of the geographical envelope of the Earth, and to identify new universal dependence. The article describes the theoretical and methodological aspects of the study. The existing approaches to the definition of information are considered, main problems of information studies and geography possibilities in the search for solutions have been highlighted. A new definition of information as an organized diversity of systems and models, terminology of systems and information studies, the conceptual model of the interaction of the information field and space, main methods of information storage have been proposed. The following has been presented: potential for the development of methods of semantic reconstruction in semiotics and archeology; determination of the age and origin of objects; importance of fundamental research information for the creation of the theory of natural and cultural heritage.